Comparison of some cytokines, acute phase proteins and citrulline levels in healthy and canine distemper infected dogs - HATIPOGLU, Durmus; DIK, Irmak; GULERSOY, Erdem (Journal of Veterinary Medical Science, 2023)
Canine distemper virus (CDV) is the etiological agent of severe disease in domestic and wild carnivores. Clinical diagnosis of CDV is challenging because of its similarity to other canine respiratory and intestinal diseases. We aimed to determine certain cytokine (interleukin [IL]-1β, IL-2, IL-4, IL-6, IL-10, and tumor necrosis factor-α [TNF-α]), interferon (IFN)-γ, canine serum amyloid A (SAA), and canine citrulline (CIT) levels for the first time in CDV-positive dogs. For this purpose, 10 CDV-positive dogs with compatible clinical findings (i.e., neurological symptoms such as tremors and myoclonus, ocular and nasal discharge, and wheezing) and 10 healthy dogs based on the clinical examinations and rapid test results were enrolled. It was observed that the CIT, INF-γ, IL-1β, IL-2, IL-6, and TNF-α levels were significantly decreased in the CDV-positive dogs than that of the healthy ones (P<0.05). As a result, it was observed that CDV causes immunosuppression and accordingly, the inflammatory response might cause decreased cytokine and acute-phase protein synthesis. Therefore, it was concluded that further investigation of inflammatory pathways and CIT interactions may provide crucial clinical information at different stages of CDV, and aforementioned parameters may serve as important biomarkers for CDV in terms of demonstrating the presence of immunosuppression.